Knowledge Acquisition: The Role of Organization’s Vision A Case of Technology-Based Start-Up in Indonesia - Naufal Al Labib Tisyadi; Dedy Sushandoyo; Retna Ayu Mustikarini Kencanasari (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
This study aims to uncover how Organization’s vision (OV) can affect Knowledge Acquisition (KA). Qualitative research method is implemented to investigate a case of KA in technology-based Start-Up, namely e-Fishery. This study's data is collected by performing semi-constructed interviews several prominent figures in the company. Data analysis is done by thematic analysis to identify emerging themes and the interrelation between them. Findings of this research suggest that OV indirectly affects KA through influencing the way organizations interact with the customers, which in turn affects KA performance. Furthermore, this study argues the positive influence of customer oriented OV to KA success. This study contributes to KA literature by providing elaboration on OV influence and its role in the interaction inside organization-customers settings. Keywords: knowledge acquisition, organization’s vision, interaction, digital start-up, innovation